2011
DOI: 10.1038/ncomms1459
|View full text |Cite
|
Sign up to set email alerts
|

Backbone rigidity and static presentation of guanidinium groups increases cellular uptake of arginine-rich cell-penetrating peptides

Abstract: In addition to endocytosis-mediated cellular uptake, hydrophilic cell-penetrating peptides are able to traverse biological membranes in a non-endocytic mode termed transduction, resulting in immediate bioavailability. Here we analysed structural requirements for the non-endocytic uptake mode of arginine-rich cell-penetrating peptides, by a combination of live-cell microscopy, molecular dynamics simulations and analytical ultracentrifugation. We demonstrate that the transduction efficiency of arginine-rich pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
272
2
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(301 citation statements)
references
References 30 publications
13
272
2
9
Order By: Relevance
“…Hence, these results are consistent with the generally accepted idea that the incorporation of guanidinium groups in a molecule facilitates its internalization through cell membrane, [60][61][62] such as in the case of cell-penetrating peptides. As previously mentioned, cell uptake studies with amino-and guanidinoglycosides had demonstrated an approximately 20-fold internalization enhancement of neomycin upon guanidinylation.…”
Section: Cell Uptake In Du-145 and Hek293 Cell Linessupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, these results are consistent with the generally accepted idea that the incorporation of guanidinium groups in a molecule facilitates its internalization through cell membrane, [60][61][62] such as in the case of cell-penetrating peptides. As previously mentioned, cell uptake studies with amino-and guanidinoglycosides had demonstrated an approximately 20-fold internalization enhancement of neomycin upon guanidinylation.…”
Section: Cell Uptake In Du-145 and Hek293 Cell Linessupporting
confidence: 90%
“…As previously mentioned, cell uptake studies with amino-and guanidinoglycosides had demonstrated an approximately 20-fold internalization enhancement of neomycin upon guanidinylation. 45 In fact, guanidinoneomycin shows similar or even better cell uptake efficiency than some polyarginine-containing peptides, 45,60,61,62 which has been attributed to the semi-rigid pre-organization of the guanidinium groups on the glycoside core. 45 Accordingly, ICP-MS accumulation studies with conjugates 2 and 3 showed the same tendency in both cell lines, since guanidinylation of the neomycin moiety leads to a compound (conjugate 3) with greater accumulation than its amino precursor (conjugate 2).…”
Section: Cell Uptake In Du-145 and Hek293 Cell Linesmentioning
confidence: 99%
“…The TAT peptide was synthetized with D-amino acids and conjugated with TAMRA as described. 29 It can be excluded that different amounts of fluorescent labeling on the different peptides play a role in the intracellular distribution, since the in vitro synthesis of peptides coupled to a resin material allows only in line addition of amino acids and the fluorophore. The pI values of the peptides and proteins were calculated using the ProtParam tool on http://web.expasy.…”
Section: Methodsmentioning
confidence: 99%
“…4A) and mistargeted the peptide to the nucleolus, which is a known feature of arginine rich peptides. 24,26 Figure 2. Design of PCNA interacting peptides (PIP).…”
Section: Resultsmentioning
confidence: 99%
“…13 Therefore, to make the PIPs membrane permeable we first covalently coupled the p21-08 PIP to a CPP derived from the HIV-1 TAT protein (TAT peptide) able to transduce into live cells and transport other peptides. [22][23][24][25] The nucleus of a cell expressing fluorescently labeled PCNA was microirradiated, which was accompanied by PCNA recruitment to the damaged site. However, the CPP sequence fused to PIP interfered with the its binding to PCNA (Fig.…”
Section: Resultsmentioning
confidence: 99%